A method for optimal cut-off grade policy in open pit mining operations under uncertain supply - Khan, Asif; Asad, Mohammad Waqar Ali (Resources policy, 2019)
Cut-off grade controls the movement of materials among mining, processing and refining stages of an open pit mining operation. The cut-off grade policy constitutes a schedule of cut-off grades and the associated quantities of materials that flow through various stages over the life of operation. This flow of materials in the system relies on the grade-tonnage curve of the mineral resource and given that the variation in grade-tonnage curve is inevitable, it is crucial that the methods that define the cut-off grade policy must consider this grade uncertainty. However, with few exceptions, a majority of these methods ignore this uncertainty in the supply of materials. This paper shares a two-stage stochastic linear programming based cut-off grade optimisation model that accounts for the grade uncertainty and maximises the net present value (NPV) subject to the production capacity constraints over the life of operation. An application of the proposed method at hypothetical and realistic cases promises higher NPV as compared to the traditional heuristic approach. •A stochastic model that defines a unique schedule of cut-off grades and flow of materials in an open pit mining operation.•The model considers a set of simulated equally probable realisations of the gradetonnage distribution.•The model demonstrates better performance as compared to traditional methods.•The model generates an optimal and risk-quantified cut-off grade policy that facilitates the decision making process.